Effect of Different Regeneration Processes on LID Degradation Mechanisms in B-doped p-type c-Si PERC Solar Cells in Industrial Production - Kübra Çelen; Alihan Kumtepe; Mete Günöven (SiliconPV Conference Proceedings, 2024)
Light-induced degradation (LID) and elevated temperature-induced degradation (LeTID) mechanisms negatively affect the performance of p-type Cz-Si-based solar cells. In this study, the degradation rates under illumination were investigated for non-metallized and metallized PERC cells with different base resistivities at different temperatures. These bifacial PERC cells are produced from own-produced ingots and wafers in a vertically integrated environment. The effect of different regeneration processes, using either illuminated annealing or direct current injection used in standard production against LID, is also investigated.